Avaliação das necessidades identificadas pelos cirurgiões-dentistas da atenção básica para o cumprimento dos indicadores em saúde bucal no município de Fortaleza, Ceará - Mendes Júnior, Francisco Ivan Rodrigues (2014)
This study had an exploratory and descriptive nature, with qualitative and quantitative approach, which sought to assess the needs identified by dentists of primary care to the fulfillment of indicators in oral health from the Program of Improvement of Access and Quality – Basic Atention of Fortaleza City, Ceará State. It was used a questionnaire containing 37 queries, with 23 closed questions and 14 semi-structured questions. The results were derived from questionnaires administered to 137 (one hundred and thirty seven) dentists from the Primary Care in Fortaleza, found in six (06) Health Regions during meetings of permanent education sponsored by municipal management. This quantitative of dentists corresponded to 70,25% of a population of 195 (one hundred and ninety-five) dentists registered in Oral Health Teams until October, 2013. The lack of motivation, the discontinuity in providing dentistry supplies, the insecurity in the clinical management of the professional related to dental prothesis, dental urgencies and diagnosis of oral mucosal changes of users were the main problems identified which interfere at the fulfillment of most of these indicators. Given the above findings, it was observed the need to invest in permanent education process, involvement of professionals in the process of planning and organization of the services, improvements in working conditions, regular deliveries of dentistry supplies, acquisition of instrumental and improvements in relations work, especially in humanization, promoting the appreciation and recognition of professional inserted therein, so that we can generate their greatest satisfaction.